Role of body mass category in the development of faulty postures in school-age children from a rural area in south-eastern Poland: a cross-sectional study. Issue 11 (7th November 2019) - Rusek, Wojciech; Leszczak, Justyna; Baran, Joanna; Adamczyk, Marzena; Weres, Aneta; Baran, Rafał; Inglot, Grzegorz; Czenczek-Lewandowska, Ewelina; Porada, Sławomir; Pop, Teresa
Abstract : Objective: The aim of the study was to assess the relationship between body mass index (BMI) and the incidence of abnormalities in selected parameters measured in the trunk area. Design: Cross-sectional studies. Setting: The research was conducted in a primary school in the Trzebownisko Municipality, a rural area in south-eastern Poland. Participants: A group of 464 children, ranging in age from 6 to 16 years (234 boys and 230 girls), was recruited to participate in the study. Outcome measures: The examination of their body postures was conducted with the use of the Zebris system. Body mass was determined using a body mass analyser Tanita MC-780 MA. BMI was calculated based on the acquired data. Results: It was noticed that the children with overweight and obesity tended to have an incorrect position of the shoulders and pelvis in comparison to children with normal body weight. It was found that greater body mass (higher BMI) coincided with a larger distance of the scapulae from the frontal plane (p=0.009). Conclusions: Increase in children's BMI produces adverse effects in the position of the shoulder blades, reflected by their greater distance from the frontal plane. Increase in BMI is not significantly related to the position of the shoulder joints or pelvis; however, the subjects with overweight or obesity presented a greater difference in the position of the shoulder joints and pelvis.